The Concept of Disability in Libyan Culture - Abulhul, Zeinab (Advances in Social Sciences Research Journal, 2023)
The author delves into the perspectives of Libyan parents regarding children with disabilities. The article highlights the impact of Libyan culture on the kind of disability and how society views children with disabilities and their parents in the Libyan community. An analytical thinking framework was used to analyze the extent to which societal culture has impacted the social lives of Libyan citizens. Some people’s attitudes toward having children with disabilities in their families or relatives are influenced by their family structure, while others are influenced by their social connections and norms. Furthermore, the article examines how members of the close Libyan family, such as mothers, fathers, and siblings, perceive disability and how their opinions affect individuals with disabilities. The aim of this article is to educate social workers about the impact of societal culture on the treatment of children with disabilities. This knowledge can help them advocate for these children with the government and utilize resources more effectively.